Post-operative effectiveness of continuous wound infiltration, continuous epidural infusion and intravenous patient-controlled analgesia on post-operative pain management in patients undergoing spinal surgery - Singh, Anshuman (Indian J Anaesth, 2017)
BACKGROUND AND AIMS: Very few studies have compared continuous wound infiltration (CWI), continuous epidural infusion (CEI) and intravenous Patient Controlled Analgesia (PCA) with morphine in spine surgery. This study compared these modalities in patients undergoing microdissectomy. METHODS: This prospective, randomized control trial was conducted on 75 patients of American Society of Anesthesiologists' physical status I or II undergoing microdiscectomy. Patients in all the three groups received morphine 1 mg IV, with a lockout period of 10 min after each bolus, and the maximum allowed dose was 15 mg/5 h postoperatively. Patients in Group A received CWI with 0.25% levobupivacaine 20 mL as bolus after extubation followed by infusion at 5 mL/h. Group B received CEI with 0.25% levobupivacaine at 5 mL/h. Patients in Group C received intravenous (IV) morphine by PCA pump only. The primary end points were static and dynamic visual analogue scores (VAS) and postoperative pain scores. Secondary observations were postoperative morphine consumption at 8 h, 24 h and 48 h, and patient satisfaction. RESULTS: Group A showed greater analgesic effects at 12 h (P < 0.02), 24 h (P < 0.03), 36 h (P < 0.008) and 48 h (P < 0.007) when compared to the other two techniques, as pain scores were less in group A as compared to group B and C. The requirement of postoperative intravenous morphine (mg) was 18 ± 12.82, 22.92 ± 9.88, 41.56 ± 8.83 for groups A, B and C after 48 h (P < 0.001). CONCLUSION: Continuous wound infiltration is an effective postoperative pain control technique with minimal side effects, after spinal surgery.